Intelligent Controllers and Optimization Algorithms for Building Energy Management towards Achieving Sustainable Development: Challenges and Prospects - Parvin K.; Lipu M.S.H.; Hannan M.A.; Abdullah M.A.; Jern K.P.; Begum R.A.; Mansur M.; Muttaqi K.M.; Mahlia T.M.I.; Dong Z.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
Buildings; Climate change; Controllers; Energy management; Energy utilization; Optimization; Planning; Renewable energy resources; Scheduling; Sustainable development; Building energy efficiency; Building energy managements; Control and optimization; Indoor environment; Intelligent controllers; Methodological approach; Optimization algorithms; Optimized controllers; Energy efficiency